Kadar Lemak, Protein Dan Sifat Sensoris Kornet dengan Substitusi Jantung Pisang - Nala Naeli Nur Fauziyah; Joko Teguh Isworo; Yunan Kholifatuddin Sya'di (Jurnal Gizi, 2017)
Banana blossom is a food rich in nutrients. During this time the benefits of banana blossomis limited to vegetable product such as jerky and "abon". Cornetsubstitution with banana blossom is one of the efforts to diversify the utilization ofbanana blossomin and have aim to produce corned with low fat content.Bananablossom when it has undergone a processing process has a fibrous texture almost the same as the texture of beef. The objective of this study was to determine the fat, protein content and sensory characteristics of corned beef with banana blossom substitution.The method used was experimental method by making corned beef with mixture ofbanana blossom material with treatment 0%, 15%, 30%, 45%,60% then, cornedyielded test fat content, protein content and sensory properties. Increasing the banana blossom substitution in corned beef causes a decrease in fat content. The lowest fat content is produced from 60% substitution of banana heart, 0.75%. The addition of banana heart also caused small decrease protein levels.Substitutiom 30 and 45% have decrease significant fat content, small decrease in protein levels and taste and texture similar to corned beef, but the color tends to turn brown. Keywords: Banana Blossom, Sensory Properties, Corned